Pengembangan Media Pembelajaran Informatika Menggunakan Canva Pada Kelas X di SMK Teknologi Muhammadiyah Bukittinggi - Nonny Nuriswatun Hasannah; Hari Antoni Musril; Darul Ilmi; Sarwo Derta (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
This study aims to develop and test the feasibility of Canva-based informatics learning media through validity, practicality, and effectiveness tests to increase the engagement and understanding of class X students at SMK Teknologi Muhammadiyah Bukittinggi. Based on observations and interviews at SMK Teknologi Muhammadiyah Bukittinggi, the informatics learning process in class X is still dominated by lecture methods and conventional media, thus not maximizing active student participation and making learning feel monotonous. This study uses a Research and Development (R&D) model with the Hannafin and Peck approach consisting of three stages: needs analysis, design, and development. The results of the validity test show that the media is in the valid category with an average score of 0.88. The practicality test by the teacher showed very high results with a value of 0.94, while the effectiveness test showed a value of 0.90, with a high effectiveness category. Based on these results, it can be concluded that the informatics learning media for class X developed using Canva is proven to be valid, practical, and effective, and has the potential to help increase student engagement and understanding in the learning process. Thus, this media is worthy of being used as a supporting alternative in informatics learning activities in schools. Abstrak